Mobility and Development, Fall 2021 : Innovations, Policies and Practices - World Bank (World Bank, Washington, DC, 2021)
Welcome to Mobility and Development: Innovations, Policies, and Practices, an online periodical launched by the World Bank's Transport Global Practice to disseminate policy-oriented and practice-ready publications affecting the transport sector worldwide. In each issue, we will explore timely topics and key trends in mobility and logistic sector influencing wider development outcomes through original, unpublished articles contributed by both World Bank staff and guest authors. The articles in the periodical aim to engage with wider audiences and internal and external stakeholders, including World Bank senior management, staff from other global practices (GPs), donors, and development partners, academia, and policy makers in low- and middle-income countries. For this inaugural issue, we have chosen to focus on Low-carbon and Resilient Mobility in a Post-COVID-19 (coronavirus) World, a theme that is perhaps unavoidable considering the pandemic and its cross-cutting impacts already reshaping the world - as we also continue efforts to diffuse the mounting threat of climate change.